The impact of education and occupation on temporary and permanent work incapacity - Nabanita Datta Gupta; Daniel Lau; Dario Pozzoli (Institute for the Study of Labor (IZA), 2012)
This paper investigates whether education and working in a physically demanding job causally impact temporary work incapacity, i.e. sickness absence, and permanent work incapacity, i.e. the inflow to disability via sickness absence. Our contribution is to allow endogeneity of both education and occupation by estimating a quasi-maximum-likelihood discrete factor model. Data on sickness absence and disability spells for the population of older workers come from the Danish administrative registers for 1998-2002. We generally find an independent role of both education and occupation on temporary work incapacity only. Having at least primary education reduces women's (men's) probability of temporary work incapacity by 16% (38%) while working in a physically demanding job increases it by 37% (26%). On the other hand, conditional on sickness absence, the effects of education and occupation on permanent work incapacity are generally insignificant.
Keywords: I12; I20; J18; C33; C35; 330; work incapacity; education; occupation; factor analysis; discrete factor model; Bildungsniveau; Beruf; Arbeitsbedingungen; Erwerbsunfähigkeit; Schätzung; Dänemark